Movement skills, perception, and physical activity of young children: a mediation analysis - Capio, Catherine M (Archīum Ateneo, 2020)
Background Fundamental movement skill proficiency and perceived physical competence have been shown to influence the physical activity of children. However, the mechanisms and patterns of their relationships in early childhood need to be investigated. This study examined the direct and indirect effects of fundamental movement skills and the mediating role of perceived physical competence on the physical activity of young children. Methods Participants were 4‐ to 6‐year‐old children (N = 230; 121 girls, 109 boys). Fundamental movement skill components (i.e., locomotor, object control) were measured using the Test of Gross Motor Development‐2; perceived physical competence was measured using the physical skills domain of the Pictorial Scale of Perceived Competence for young children; and physical activity was monitored using pedometers over a 5‐day period (n = 115). Conditional process analysis was performed to examine mediation. Results Object control skill proficiency had a significant positive effect on perceived physical competence (B = 0.28, P = 0.02), and a significant positive effect on daily step counts (B = 0.18, P = 0.04). Perceived physical competence had a significant negative effect on daily step counts (B = −0.31, P = 0.003) and mediated the indirect effect of object control skills on daily step counts (B = −0.09, 95% confidence interval: −0.17 to −0.002). Conclusions Object control skill proficiency had a significant direct effect on physical activity, and perceived physical competence mediates an indirect effect. The findings contribute to the evidence base supporting the development of object control skills as a factor that enables adequate physical activity in young children.